Sistem Sortir Batang Rokok Pada Konveyor - Khofifatul Yadayna (Jurnal Jaringan Telekomunikasi, 2020)
Kretek cigarettes are a type of cigarette that is still in demand today. The manufacturing of kretek cigarettes in factories still has limitations, especially in the process weighing cigarettes per stick. From this problem, a tool is needed to separate cigarettes based on the weight of the cigarette that has been determined per stick. And the results of the cigarette weight sorter can be monitored via the website to reduce errors in the size of the clove cigarette. The method used in this study is to make a cigarette sorting tool using a conveyor with a DC servo motor component as a driving force for the conveyor to be 3 parts by weight, namely parts weigh <1.5 grams, parts weight> 1.5 grams and parts = 1.5. gram. Based on the results of the study, 1 pack of cigarettes where each pack contains 12 cigarettes shows that there are 2 cigarettes <1.5 grams, 7 cigarettes> 1.5 grams and 3 cigarettes corresponding to 1.5 grams. The results of the study indicate that the manufacture of a cigarette sorting system on the conveyor can help the cigarette weighing process to be more precise.